Theoretical and Practical Reflections on Specialized Lexicography in African Languages - Dion Nkomo (Lexikos, 2019)
In this article, reflections are made on some specialized lexicographical/terminographical resources being produced in African languages. The resources are produced in order to contribute towards the intellectualization of those languages for expanded functional usage. The article focuses on lemma selection, provision of data/information for included lemmata and structural aspects of the surveyed resources. With regard to the first area of focus, the article identifies the lack of a systematic approach to lemma selection, which undermines the potential of the resources as communicative and cognitive tools in specialized subject fields and disciplines. Secondly, regarding the provision of data categories, instances of insufficient information and cases of inclusion of irrelevant information are identified, both of which have implications for the functional value of the resources within specialized domains. Finally, reflections on aspects of dictionary structure indicate sub-standard structural designs which affect the user-friendliness of the resources, but some innovative structural designs are also identified. Overall, the article argues for a stronger lexicographic orientation in terms of the theoretical underpinnings guiding the production of specialized lexicographical/terminographical resources in African languages.